Risk Factors for Development of Rhegmatogenous Retinal Detachment in Patients with Uveitis. (19th May 2019) - Kunavisarut, Paradee; Srisomboon, Titipol; Patikulsila, Direk; Choovuthayakorn, Janejit; Watanachai, Nawat; Chaikitmongkol, Voraporn; Pathanapitoon, Kessara; Rothova, Aniki
ABSTRACT: Purpose : To describe risk factors for development of rhegmatogenous retinal detachment (RRD) in patients with uveitis. Methods : We performed a retrospective review of 411 consecutive human immunodeficiency virus-negative patients with uveitis (571 affected eyes) and report on prevalence, risk factors and visual outcomes of patients with RRD. Results : Prevalence of RRD was 7% of all patients with uveitis. Multivariate analysis revealed that posterior uveitis and panuveitis were associated with RRD ( P  = 0.001). Strong association between RRD development and infectious uveitis was also observed ( P  = 0.009). Acute retinal necrosis (ARN) was firmly associated with RRD development ( P  = 0.016). Although anatomical success was obtained, functional outcome was poor. Poor visual outcomes at 6-month and 1-year follow-up were associated with initial VA < counting fingers ( P  = 0.05, P  = 0.044). Conclusions : Prevalence of RRD in uveitis was 7% and development of RRD was encountered in posterior and panuveitis. Infectious uveitis (specifically ARN) formed a high risk for RRD.